Development of Polymeric Matrices Based on Banana Plant Extracts for Biomedical Applications - Nascimento, Rosa Estela Abreu do (2019)
The aim of this thesis was the development and characterization of polymeric matrices, in the form of film or gels, using compounds extracted from banana plant leaves and pseudostem, in order to evaluate their potential for biomedical applications and eventually for food applications, accordingly to the features of the obtained matrices. Different extracts were obtained through Batch-Solid Liquid and Soxhlet extraction, with different extraction periods and different drying temperatures of the samples. After determination of Total Phenolic Content (TPC) and antioxidant activity, by Folin-Ciocalteau and 2,2-difenil-1-picrilhidrazilo (DPPH) methods, respectively, the extracts were characterized by High Pressure Liquid Chromatography (HPLC) and Liquid Chromatography-Mass Spectroscopy (LC-MS). The polymeric matrices were prepared using cellulose extracted from banana plant pseudostem (PS) or commercial cellulose (hydroxyethyl cellulose – HEC), glucose (G) and/or urea (U) and phenolic compounds extracted from banana plant leaves (L) as bioactive compounds. The prepared matrices were characterized by Scanning Electron Microscopy (SEM), X-Ray Diffraction (XRD), Differential Scanning Calorimetry (DSC), Thermogravimetric Analysis (TGA), Fourier Transformed Infrared spectroscopy (FTIR), contact angle, swelling, mechanical properties, rheology and gas permeation studies. The obtained results showed that the banana plant leaves present a TPC higher than banana peel, pulp and banana plant pseudostem, being the Batch-Solid Liquid with 3 days extraction and leaves dried at 40°C (BSL_3_40) allowed the highest TPC. It was also possible to extract cellulose from banana plant pseudostem. In general, the synthetized matrices were hydrophilic and just the HEC matrices exposed to 84% aw present a dense structure. The plasticizers and water activity showed to influence the matrices flexibility, which could be controlled accordingly to the desired matrices application.